Utilisation of Food and Woodworking Production By-products by Composting - Uldis Viesturs; Andrejs Berzins; Silvija Strikauska; Dzidra Zarina (Bioautomation, 2004)
The purpose of the study was to develop laboratory-scale technologies for composting milk/cheese whey, spent liquor, brewery yeast, fish processing by-products, etc., adding these by-products and special microorganism associations to the basic material - sawdust, bark, etc., also arranging different experimental composting sites. Two Trichoderma strains (Tr. lignorum, Tr. viride) and a nitrification association for regulating the circulation of nitrogen-ammonification and nitrification processes were applied. Monitoring of the composting quality was realised by microbiological and chemical analyses, and biotests for compost quality (toxicity) assessment. For purifying the polluted air from the composting facilities, the biofiltration technique was realised in a modified SSF system. Biodegradation of ammonia was investigated in a two-stage system with the inert packing material - dolomite broken bricks, and hemoautotrophic microorganisms: DN-1 (Pseudomonas sp.), DN-2 (Nitrosomonas sp.), DN-3 (Nitrobacter sp.) and DN-13 (Sarcina sp.). For hydrogen sulphide biodegradation, Thiobacillus thioparus-3 was immobilised on glass bricks as the carrier material. Biodegradation efficiency of hydrogen sulphide was 87%. Biodegradation of ammonia in the first step in the two-stage system reached 77%, degradation of the gas remaining in the second step was 75%. Compost's quality was similar to black soil - brown-coloured, with good soil odour and without toxic compounds.